Effect of spraying bupivacaine and dexamethasone on postoperative pain of total extraperitoneal hernioplasty: a retrospective analysis - Ozer, Mehmet; Ulusoy, Serap; Kılınç, İbrahim; Oruç, Mustafa (International Surgery Journal, 2023)
Background: Several studies on the reduction of pain with the use of local anesthetics after laparoscopic hernia surgeries have been published. We aimed to analyze the results of local anesthesia applied to the patients by retrospectively scanning the files of patients who underwent total extraperitoneal laparoscopic hernioplasty for inguinal hernias. Methods: The files of patients who underwent TEP laparoscopic hernioplasty for inguinal hernias between March 2019 and November 2022 in Ankara Bilkent city hospital general surgery clinic were retrospectively scanned. The pain scoring records in the observation forms of these patients and the analgesics administered were recorded. Results: A total of 374 and 210 patients underwent unilateral and bilateral TEP laparoscopic hernioplasty, respectively. All of the patients, 232 were not administered any local anesthesia, 186 were administered bupivacaine, and 166 were administered bupivacaine+dexamethasone. When the VAS scores of the patients in both main groups were compared, significant differences were found in VAS scores between patients who received bupivacaine and bupivacaine+dexamethasone and those who did not (p<0.036 and p<0.025). No difference was found between patients who received only bupivacaine and those who were given bupivacaine+dexamethasone. Conclusion: In patients who underwent TEP laparoscopic hernioplasty, spraying bupivacaine into the preperitoneal area after surgery was found to be significantly effective in reducing postoperative pain. The benefits of adding dexamethasone to bupivacaine have not been established.